(untitled) (Journal of Philosophy Culture and Political Science, 2022)
The policy of a number of countries that have embarked on the path of legalized mobile phone tracking to ensure compliance with quarantine restrictions on people infected with COVID-19 has generated heated discussions in the scientific community about the threats posed by modern digital technologies. The excessive use of digital technologies has led not only to the strengthening of the powers of the State in public life, but also threatened the privacy and confidentiality of personal data. However, the beginning of these extraordinary powers of the State was laid back in 2001, when the global war on terrorism unfolded. It is from this moment that the beginning of the process of the decline of the rule of law, which led to the restriction of the personal space of citizens, should be dated. Today, the governments of a number of countries are seen to be inclined to use anti-terrorist measures to visualize a virtual threat as an internal threat, which often serves as an excuse to strengthen the system of control over their own citizens. While in the United States, the member states of the European Union, Russia and a number of other countries, this policy is now mainly used to justify the violation of the confidentiality of personal data, in China this policy has intensified so much that it has actually led to the surveillance and persecution of political dissent and discrimination against Muslim ethnic minorities. In fact, China has launched an invasive system of internal surveillance of its own citizens, which causes serious concern to the world community and human rights organizations, who rightly fear a violation of the balance of interests between state control of citizens and the security of personal data. The strengthening of state control over citizens has recently been more and more clearly observed in Kazakhstan. The public of the country is concerned about the facts of violation of the confidentiality of personal information and privacy. Keywords: Kazakhstan, Russia, China, digital technologies, Internet space, telecommunications industry, control over citizens, privacy, confidentiality of personal data.